2021
DOI: 10.3390/brainsci11111544
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Individuals at Clinical High-Risk of Psychosis in the General Population and Clinical Samples: Systematic Review and Meta-Analysis

Abstract: (1) The consistency and magnitude of the prevalence of Clinical High-Risk for Psychosis (CHR-P) individuals are undetermined, limiting efficient detection of cases. We aimed to evaluate the prevalence of CHR-P individuals systematically assessed in the general population or clinical samples. (2) PRISMA/MOOSE-compliant (PROSPERO: CRD42020168672) meta-analysis of multiple databases until 21/01/21: a random-effects model meta-analysis, heterogeneity analysis, publication bias and quality assessment, sensitivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 56 publications
0
34
2
Order By: Relevance
“…On the other hand, it is not clear whether the dissociative symptoms did not develop in parallel over time in patients with schizophrenia from the perspective of hospitalizations and in the process of treatment with various antipsychotic drugs. Some authors in a study found in the general population up to 1.7% of people at high risk of developing psychosis ( 57 ). No data have been established on the level of dissociative symptoms in them.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is not clear whether the dissociative symptoms did not develop in parallel over time in patients with schizophrenia from the perspective of hospitalizations and in the process of treatment with various antipsychotic drugs. Some authors in a study found in the general population up to 1.7% of people at high risk of developing psychosis ( 57 ). No data have been established on the level of dissociative symptoms in them.…”
Section: Discussionmentioning
confidence: 99%
“…SCZ is a mental disorder characterized by abnormally interpret reality, hallucinations, delusions, apathy, lack of social functioning, and extremely disordered thinking and behavior. Cognitive symptoms, including concentration and attention difficulties, as well as memory impairments, can be subtle [ 357 ]. Cognitive deterioration in patients with SCZ has been linked to vitamin D deficiency which may directly affect processing speed [ 358 ].…”
Section: Diseases Linked To Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Schizophrenia SCZ is a mental disorder characterized by abnormally interpret reality, hallucinations, delusions, apathy, lack of social functioning, and extremely disordered thinking and behavior. cognitive symptoms including difficulty in concentration and attention, and memory impairments can be subtle [324]. SCZ is generally considered to be a neurodegenerative disorder with neurodevelopmental antecedents.…”
Section: Bipolar Disordermentioning
confidence: 99%